Peran Kualitas Pelayanan dan Kepercayaan Konsumen dalam Membentuk Kepuasan Pelanggan Jasa Servis Iphone Nonresmi - Lia Yuliani; Yenni Kurnia Gusti (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to analyze the influence of service quality and consumer trust on customer satisfaction levels in iPhone service providers at Pacmac Pacitan. Low customer satisfaction arising from inconsistencies in service results, limited information, and public doubts about unofficial service providers is a problem in this study. The research was conducted through a quantitative approach with data processing using multiple linear regression analysis to comprehensively determine the relationship between variables. An analytical approach was used to assess the extent to which service quality and consumer trust shape customer perceptions and experiences of the services provided. The results of the regression analysis showed that service quality (β = 0.437; p < 0.001) and consumer trust (β = 0.295; p = 0.002) have a positive and significant effect on customer satisfaction, with an Adjusted R² value of 0.471. Consumer trust has been shown to provide an important contribution and is a major factor in the use of electronic device service providers. Together, the variables of service quality and consumer trust have a significant influence in shaping customer satisfaction levels, so that improving service quality and strengthening trust are strategies that need to be prioritized.